Jurisdiction and Arbitration Clauses in Maritime Transport Documents A Comparative Analysis - Sparka, Felix; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Jurisdiction and arbitration clauses are two different mechanisms that help to ensure impartiality and predictability in international dispute resolution. Despite their benefits, these clauses can be inconvenient for parties that are forced to litigate before distant fora. Moreover, particular problems arise in the context of maritime transport documents. Based on a broad comparative approach, this study seeks to explain the existing rules within their legal context and to develop a coherent system for such clauses, which takes into account the underlying interests as well as economic theory. While offering detailed answers to most issues surrounding jurisdiction and arbitration clauses in maritime transport documents, the book confronts the fundamental question of the limits of freedom of contract in an international setting.
The Legal Framework for Choice of Forum Clauses in Maritime Transport Documents -- Bills of Lading and other Maritime Transport Documents -- Common Types of Choice of Forum Clauses in Maritime Transport Documents -- Classification of Choice of Forum Clauses and their Separability from the Main Contract -- Formal Requirements and the Incorporation of Choice of Forum Agreements -- Inconvenient and Unfair Choice of Forum Clauses -- The Effect of Mandatory Liability Rules on the Enforcement of Choice of Forum Clauses -- The Effect of Choice of Forum Clauses on Third Party Cargo Receivers -- Future Developments #x2013; the Hamburg Rules and Beyond -- General Observations and Conclusions.
Keywords: Law; Private international law; Conflict of laws; International law; Comparative law; Law of the sea; Mediation; Dispute resolution (Law).; Conflict management; Law; Private International Law, International & Foreign Law, Comparative Law; Law of the Sea, Air and Outer Space; Dispute Resolution, Mediation, Arbitration; Electronic books